Sexual behavior of Acanthogonatus centralis (Araneae: Mygalomorphae: Nemesiidae) from Argentina, with some notes on their burrows - Ferretti, Nelson Edgardo (2011)
Acanthogonatus centralis Goloboff 1995 is a Neotropical nemesiid distributed in hilly zones of central Argentina. The biology of the Nemesiidae is almost unknown. We describe the courtship and mating of A. centralis based on eight observed matings (three males and five females). Male courtship involved scratching and beating the ground. These behaviors have not been observed in other mygalomorph spiders and are here described for the first time. After contacting female silk, males stretched the web. Males manipulated their pedipalps and spasmodically beat their legs over the female. The mating position was typical of mygalomorph spiders. Females remained active during copulation by making body jerks and struggling. The body jerks of females could be stimulating the male to renew palpal insertion. In addition to describing this spider family's mating behavior, we also include some notes on their shelters. The tunnel-webs observed in the field had no branches, only one entrance, and a short burrow. Adult males are capable of constructing tunnel-webs, but they are quite different from those of juveniles and females, lacking the short burrow. © 2011 The American Arachnological Society.